Avaliação da importância do fotorreparo de DNA em anfíbios - Londero, James Eduardo Lago (2019)
Amphibians have suffered a widespread population decline across the globe. About 40% of existing amphibian species are threatened with extinction. Solar ultraviolet (UV) radiation (280-400 nm) has the capacity to form cytotoxic and mutagenic lesions in the amphibian genome, which may compromise the performance and fitness of these animals. Factors such as the decrease of stratospheric ozone, climate changes, deforestation and decrease of organic matter in water bodies have increased the incidence of solar UV radiation upon amphibian breeding sites. In contrast, in order to minimize the harmful effects of UV-induced lesions on their genome, amphibians have mechanisms capable of repairing them, such as photorepair (or photoreactivation), which involves the absorption of light (350-700 nm) by means of enzymes called photolyases and the transfer of electrons to the lesions, thus removing them. However, photorepair capacity varies among species, and the inefficiency of this mechanism is a possible determinant factor for population decline of UV-sensitive species. Taking this into account, the general objective of this work was to evaluate the importance of DNA photorepair in amphibians. First, the biological responses of amphibians to UV-induced DNA damage, which include photorepair capability, have been discussed through a broad review of existing literature on this topic. The results show that only three out the 21 studies found directly evaluated the UV-induced DNA lesions in vivo. As a consequence, DNA repair mechanisms are very few studied and understood. Thus, the importance of DNA photorepair for the maintenance of the feeding performance of forest specialist tadpoles previously exposed to a low environmental dose of UVB radiation (280-315 nm) was evaluated through a controlled experimental study with a species of treefrog threatened with extinction [Boana curupi (Garcia, Faivovich and Haddad, 2007); Anura; Hylidae]. The results demonstrate that UVB radiation negatively impacted tadpole weight due to reduced food consumption, which in turn was a consequence of the genotoxic impact of UVB. An additional treatment with visible light (post-UVB) suggested a low efficiency of DNA photorepair in this species, since body weight and food consumption activity remained affected. In addition, in silico analyzes were conducted with the objective of understanding the molecular basis of amphibian photolyases. Homology analyzes were performed with sequences of amphibian photolyases. Only annotated and accurate sequences were obtained from GenBank, BLASTp and tBLASTn (NCBI). The results demonstrate interspecific variations in the occurrence of these enzymes and the possible bad annotation of some sequences. From these results, future perspectives are discussed. The present dissertation demonstrates that there is still a lack of understanding of amphibian photolyases, and that possible new avenues on this subject must be traced in order to better elucidate the role of photorepair in amphibians. Therefore, the contribution of solar UV radiation to the decline of amphibians, and the importance of DNA photorepair to avoid the UV-induced genotoxic effects on amphibian species may become more evident in the near future.